MO047: Biallelic pathogenic variants in ROBO1 associate with syndromic CAKUT. (3rd May 2022) - Münch, Johannes; Engesser, Marie; Schönauer, Ria; Hamm, J Austin; Akay, Gulsen; Tüysüz, Beyhan; Shirakawa, Toshihiko; Dateki, Sumito; Claus, Laura; van Eerde, Albertien M; Wagner, Timo; Bergmann, Carsten; et al.
Abstract: BACKGROUND AND AIMS: Congenital anomalies of the kidney and urinary tract (CAKUT) represent the most common cause of chronic kidney failure in children. Despite growing knowledge of the genetic causes of CAKUT, the majority of cases remain etiologically unsolved. Genetic alterations in roundabout guidance receptor 1 (ROBO1) have been associated with neuronal and cardiac developmental defects in living individuals. Although Slit-Robo signaling is pivotal for kidney development, diagnostic ROBO1 variants have not been reported in viable CAKUT to date. METHOD: We collected phenotypic data of all participants. Genetic analysis was conducted by either exome or whole genome sequencing, respectively. We used Sanger sequencing for variant confirmation and segregation analysis and performed in-silico analysis of identified missense variants. In an ENU-induced mouse model, we examined mice with the mutation Robo1 Ile270Thr/Ile270Thr . RESULTS: By next-generation-sequencing methods, we identified six unrelated individuals and two non-viable fetuses from Germany, France, Turkey, Japan and the USA with biallelic truncating or combined missense and truncating variants in ROBO1 . Renal and genitourinary manifestation included unilateral or bilateral renal agenesis, vesicoureteral junction obstruction, vesicoureteral reflux, posterior urethral valve, genital malformation and increased renal echogenicity. Further clinical characteristics were remarkably heterogeneous, including neurodevelopmental defects, intellectual impairment, cerebral malformations, eye anomalies, and cardiac defects (Figure 1 ). By in-silico analysis, we determined the functional significance of identified missense variants and observed absence of renal ROBO1 expression in both human and murine mutant tissues (Figure 2 ). CONCLUSION: This study describes six live-born and two non-viable individuals with syndromic CAKUT due to probably deleterious ROBO1 variants. While its expression in multiple tissues may explain heterogeneous organ involvement, variability of kidney disease suggests gene dosage effects due to a combination of null alleles with mild hypomorphic alleles. In conclusion, comprehensive genetic analysis in CAKUT should include ROBO1 as a new cause of recessively inherited disease. Conversely, in patients with already established ROBO1-associated cardiac or neuronal disorders, screening for renal involvement is indicated.